Reduced phonemic fluency in progressive supranuclear palsy is due to dysfunction of dominant BA6 - Isella, Valeria; Licciardo, Daniele; Ferri, Francesca; Crivellaro, Cinzia; Morzenti, Sabrina; Appollonio, Ildebrando; Ferrarese, Carlo (Frontiers in Aging Neuroscience, 2022)
Background: Reduced phonemic fluency is extremely frequent in Progressive Supranuclear Palsy (PSP), but its neural correlate is yet to be defined. Objective: We explored the hypothesis that poor fluency in PSP might be due to neurodegeneration within a dominant frontal circuit known to be involved in speech fluency, including the opercular area, the superior frontal cortex (BA6), and the frontal aslant tract connecting these two regions. Methods: We correlated performance on a letter fluency task (F, A, S, 60 sec for each letter) with brain metabolism as measured with Fluoro-deoxy-glucose Positron Emission Tomography, using Statistical Parametric Mapping, in 31 patients with PSP. Results: Reduced letter fluency was associated with significant hypometabolism at the level of left BA6. Conclusion: Our finding is the first evidence that in PSP, as in other neurogical disorders, poor self-initiated, effortful verbal retrieval appears to be linked to dysfunction of the dominant opercular-aslant-BA6 circuit.